Identification of Atypical Peri-Nuclear Multivesicular Bodies in Oxidative and Glycolytic Skeletal Muscle of Aged and Pompe's Disease Mouse Models - Neel, Brian A.; Zong, Haihong; Backer, Jonathan M.; Pessin, Jeffrey E. (Frontiers in Physiology, 2015)
Muscle wasting that occurs during aging or from disease pathology presents with an accumulation of lipid species termed ceroid or lipofuscin. This unique species of lipid has been characterized in various cell types but its properties and organization in skeletal muscle remains unclear. Using immunofluorescence and transmission electron microscopy, we were able to visualize and characterize an atypical lipid storing organelle in skeletal muscle. White myofibers contain two organelles at each pole of the myonuclei and red myofibers contain many of these structures in and around the perinuclear space. These organelles contain markers for late endosomes, are morphologically similar to multivesicular bodies, store lipid, and hypertrophy in aged muscle and a model of muscle wasting with an accumulation of large amounts of lipofuscin. Rapamycin treatment reduces the multivesicular body hypertrophy, restores late endosomal protein markers, and also increases the number and intensity of lipofuscin deposits. Together, these data demonstrate for the first time a perinuclear organelle in skeletal muscle that hypertrophies in muscle wasting phenotypes and is involved in endocytic lipid storage.